Somatic Embryogenesis in the Medicago truncatula Model: Cellular and Molecular Mechanisms - Rose, Ray J. (Frontiers in Plant Science, 2019)
Medicago truncatula is now widely regarded as a legume model where there is an increasing range of genomic resources. Highly regenerable lines have been developed from the wild-type Jemalong cultivar, most likely due to epigenetic changes. These lines with high rates of somatic embryogenesis (SE) can be compared with wild-type where SE is rare. Much of the research has been with the high SE genotype Jemalong 2HA (2HA). SE can be induced from leaf tissue explants or isolated mesophyll protoplasts. In 2HA the exogenous phytohormones 1-naphthaleneacetic acid (NAA) and 6-benzylamino purine (BAP) are central to SE. However, there are interactions with ethylene, abscisic acid (ABA) and gibberellic acid (GA) which produce maximum SE. In the main, somatic embryos are derived from dedifferentiated cells, undergo organellar changes and produce stem-like cells. There is evidence that the SE is induced as a result of a stress and hormone interaction and this is discussed. In M. truncatula there are connections between stress and specific up-regulated genes and specific hormones and up-regulated genes during the SE induction phase. Some of the transcription factors have been knocked down using RNAi to show they are critical for SE induction (MtWUSCHEL, MtSERF1). SE research in M. truncatula has utilised high throughput transcriptomic and proteomic studies and the more detailed investigation of some individual genes. In this review these studies are integrated to suggest a framework and timeline for some of the key events of SE induction in M. truncatula.